The future of digital justice - HARTUNG, Dirk (Institutional Knowledge at Singapore Management University, 2022)
Justice systems worldwide are under increasing pressure as legal complexity rises andmore people rightfully demand access to justice. Digital transformation is the key forcourts to keep pace. Digital justice is an immense chance to improve the lives ofmillions of people, but only if the technology is understood and implemented fast.Drivers of Digital JusticeGlobally, the digitalization of justice systems is just beginning and generally laggingbehind the digital transformation of the rest of society. This has led to a widening gapbetween the expected user experience for both consumers and businesses and theactual services provided by the courts.Status quo of Digital Justice TransformationThe current state of digital justice can be understood using an adapted version of thethree-layer framework previously developed for private legal technology: It differenti-ates between enabler, process support, and substantial law solutions. Compared toother parts of the legal system, courts and public offices are several years behind intechnology adoption. Despite recent incentives to innovate during the COVID-19 pan-demic, even economically strong countries such as Germany risk missing the boat whenit comes to future readiness. Insufficient hardware and software infrastructure, budgetissues, a hindering mindset, and fear of personal disadvantages among stakeholdersare all to blame.International Best PracticesAustria, Canada, Singapore, and the United Kingdom are leading in justice digitalization.They demonstrate several key traits that help make for the successful digital transfor-mation of a justice system. Adoption of software development best practices from theprivate sector, early, strong, and decisive leadership, user-centricity, and openness toprocess optimization and data-based strategies have helped them manage the relevantchanges.Future of Digital JusticeDigital justice enables faster, more efficient case management and the effective resolu-tion of legal conflicts, better working conditions within courts, and greater access to thelegal system. Countries that strive for these positive results require a bold vision at theoutset, a purposefully designed governance, and an adapted legal framework to ring inthe required paradigm shift. For help, they can tap into a young generation of judges,clerks, and other civil servants eager to bet on technology to advance their country andtheir careers.